17 Management of neuropsychiatric SLE. (6th April 2022) - Amoura, Zahir
Abstract : Case 1: A 38-year-old woman with NPSLE A 38-year-old patient presented for a follow-up consultation for her systemic lupus erythematosus (SLE). She was on 5 mg/day of prednisone and hydroxychloroquine 400 mg/day. She describes headaches that have been present for a month. On examination her pulse rate was 80 BPM, BP 122/74mmHg and temperature: 37°C. Neurological examination was normal. Respiratory, cardiovascular, joint and skin examinations were normal. Discussion Points: What course of action do you propose? Case 2: A 31-year-old woman with SLE and acute psychosis A 31-year-old woman hospitalised in January 2022. She has had a medical history of SLE diagnosed in December 2018. Malar rash (acute cutaneous lupus), photosensitivity, diffuse alopecia, oral ulcerations, bilateral pleurisy, proteinuria with a kidney biopsy showing Class IV glomerulonephritis according to ISN classification, positive anti-double stranded DNA antibody test (Farr assay 78 UI; N< 9 UI), low C3 fraction, positive lupus anticoagulant, negative anticardiolipin antibody ELISA (IgG and IgM), negative anti-B2GP1 ELISA (IgG and IgM). She had no thrombotic or obstetrical history. She first received three pulses of methylprednisolone (1000 mg each) followed by oral prednisone 0.5 mg/kg/day + mycophenolate mofetil (MMF) 2 g/day + ACE inhibitors. Steroids were tapered to 5 mg/day at 6 months. Daily proteinuria decreased to 1 g at Month 3 and 0.5 g at Month 6. C3 returned to normal level at Month 6. Steroids were stopped at Month 24 and hydrocortisone 20 mg/day was given instead. MMF 2 g/day was decreased to 1 g/day in September 2015. She was hospitalised in January 2022 for altered sleep-wake cycles, hyperactivity, intense anxiety, ideas of persecution and auditory hallucinations. She had no arthritis and no mucocutaneous manifestation. Her physical examination was normal with no neurological abnormalities. Laboratory test showed: normal red and white blood cell and platelet counts; creatinine: 69 µmol/L; proteinuria: 0.2 g/L, Urine tests were sterile with no haematuria, creatininuria: 8.9 mmol/L = ratio 0.02 g/mmol; albuminemia: 43 g/L; C reactive protein: <5 mg/L. Farr assay 18 UI; N< 9 UI, normal C3 fraction. At that time, she was treated with prednisone 5 mg/day + MMF 1 g/day. A diagnosis of acute psychosis given done by the psychiatrist. Learning Objectives: Describe how to manage headaches in patients with SLE Describe how to manage myelitis in patients with SLE Describe how to manage psychiatric manifestations in patients with SLE